The influence of achievement motivation on learning achievement of Introduction to Accounting course - Reyna Karlina; Yon Rizal; Pujiati Pujiati; Albet Maydiantoro (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to determine the influence of achievement motivation variable on learning achievement in Introduction to Accounting course of Economic Education students at the University of Lampung. The study employed a descriptive method using an ex-post facto approach and a survey with a population of 170. The research sample was determined through a purposive sampling with a total of 119 respondents. The data collected through a questionnaire were processed using SPSS to run partial hypothesis testing through t-test and simultaneous F-test. The results of this study indicate that there is an influence of achievement motivation on learning achievement in Introduction to Accounting course among Economic Education students at the University of Lampung.